Calpain Inhibition Restores Autophagy and Prevents Mitochondrial Fragmentation in a Human iPSC Model of Diabetic Endotheliopathy - Sang-Bing Ong (Stem Cell Reports, 2019)
Summary: The relationship between diabetes and endothelial dysfunction remains unclear, particularly the association with pathological activation of calpain, an intracellular cysteine protease. Here, we used human induced pluripotent stem cells-derived endothelial cells (iPSC-ECs) to investigate the effects of diabetes on vascular health. Our results indicate that iPSC-ECs exposed to hyperglycemia had impaired autophagy, increased mitochondria fragmentation, and was associated with increased calpain activity. In addition, hyperglycemic iPSC-ECs had increased susceptibility to cell death when subjected to a secondary insult—simulated ischemia-reperfusion injury (sIRI). Importantly, calpain inhibition restored autophagy and reduced mitochondrial fragmentation, concurrent with maintenance of ATP production, normalized reactive oxygen species levels and reduced susceptibility to sIRI. Using a human iPSC model of diabetic endotheliopathy, we demonstrated that restoration of autophagy and prevention of mitochondrial fragmentation via calpain inhibition improves vascular integrity. Our human iPSC-EC model thus represents a valuable platform to explore biological mechanisms and new treatments for diabetes-induced endothelial dysfunction. : In this article, Ong and colleagues used human induced pluripotent stem cell-derived endothelial cells (iPSC-ECs) as a novel disease modeling platform to study the effects of diabetes on vascular dysfunction and provided the cause for calpain inhibitors as an anti-diabetic and cardioprotective drug. Keywords: diabetes, endothelial dysfunction, iPSC, iPSC-ECs, calpain, autophagy, mitochondrial morphology, ischemia-reperfusion injury